CULTURE, SOCIETY, IDEAS, AND INNOVATION OF GENERAL EDUCATION SUBJECT OF STUDENTS IN THE NOW NORMAL: A CONCEPT AND DEVELOPMENT IN TEACHING (Isagoge - Journal of Humanities and Social Sciences, 2022)
The study aims to examine the culture, society, ideas, and innovation (CSII) of General Education subjects of students in the now normal concept and development in teaching. It also identifies the core competency of culture, society, ideas, and innovation of general education subject of students in the now normal in the area of cognitive knowledge, soft skills, hard skills, and specific discipline knowledge and the concept and development of teaching as student-centred learning culture in terms of digital literacy, effective communication, and critical thinking framework, outcome-based learning, inquiry and collaborative learning, and authentic assessment learning. The study employs descriptive quantitative research design. It measures the educational phenomena of the study on the core competency of culture, society, ideas, and innovation of general education subjects of students in the now normal and concept development. Random sampling technique is utilised in the study. The study comprised Seven Hundred (700) respondents only from the selected students in the General Education Subject.             Results show that core competency on cognitive knowledge provides creative thinking, critical thinking, coordination, self-reflection, making references, and reasoning, show that soft skills are attributed to communication, collaboration, creative thinking, and time management in the core competency of learning, show that hard skills specify the role and task needed for the ability of skills and competency, show that specific discipline knowledge explores the defining core competency and discipline for ideas in various levels of outcome in learning, show that concept and development of teaching in terms of digital literacy, effective communication, and critical thinking framework develop a sustainable skills proficiency in digital technology literacy, effective communication, and framework of critical thinking, show that outcome-based learning promotes order of higher thinking skills and curriculum acquisition on conventional requirement information ability in learning, show that inquiry and collaborative learning involves inquiry based learning and collaborative student involvement through group learning for the collective task of students, and show that authentic assessment learning stimulates student ability and assessment effectively and efficiently in complex tasks, skills, and knowledge.            Findings show that there is no significant correlation between the core competency of culture, society, ideas, and innovation of general education subjects of students in the now normal and the concept and development of teaching as student-centred and learning culture among the respondents.